An Incentive Strategy of Shiftable Load Participation in Demand Response Based on User Electricity Preference - Li, Wei; Han, Ruidi; Zhang, Jie; Sun, Chenjia; Fu, Peng (Frontiers in Energy Research, 2022)
China has promoted the development of the new energy power generation industry since 2013. However, the high proportion of unique energy access to the Grid brings greater volatility and uncertainty. One effective way to solve the above problems is to incentivize shiftable loads(SLs) to demand response(DR). The low enthusiasm of SLs lies in the lack of an effective incentive mechanism and strategy. Because the SLs' initiatives participating in the DR are closely related to its structure of comfort and economic preference, we divided SLs into economical users(EUs), standard users(SUs), and comfortable users(CUs). Considering the balance of the benefits between the load aggregator(LA) and SLs and the impact of resource scarcity, we build the optimal incentive model based on the principal-agent theory under the case of symmetry and asymmetry information. Based on MATLAB simulation, we have the following suggestions for LA: (1) In terms of dispatch sequence, LA should dispatch SUs first, then EUs and CUs, (2) In the setting of retained earnings, EUs should be the most, followed by SUs and the least is CUs, (3) In terms of incentive intensity, CUs need the most incentive, EUs need middle, and SUs need the least, (4) LA needs to adjust the intensity of incentive contracts according to the scarcity of resources, (5) LA should also improve their service to reduce users' risk aversion to strengthen their effort level.